Analytical corrections of banding artifacts in driven equilibrium single pulse observation of T2 (DESPOT2). Issue 6 (30th December 2015) - Jutras, Jean‐David; Wachowicz, Keith; De Zanche, Nicola
Abstract : Purpose: DESPOT2 is a single‐component T 2 mapping technique based on bSSFP imaging. It has seen limited application because of banding artifacts and magnetization transfer (MT) effects. In this work, acquisitions are optimized to minimize MT effects, while exact and approximate analytical equations enable automatic correction of banding artifacts within the T 2 maps in mere seconds. Theory and Methods: The technique was verified on an agar phantom at 3 tesla. The T 2 resulting from four different data combination techniques was compared with the T 2 from CPMG. Two comparable DESPOT2 scan protocols (short vs. long TR / T RF ) designed to minimize MT effects, were tested both in the phantom and in vivo. A third protocol was tested in the brain of 8 volunteers and analytical correction schemes were compared with DESPOT2‐FM. Results: The T 2 measurements in agar agree with CPMG within ∼7% and in vivo results agree with values reported in the literature. The approximate analytical solutions provide increased robustness to hardware imperfections and higher T 2 ‐to‐noise ratio than the exact solutions. Conclusion: New analytical solutions enable fast and accurate whole‐brain T 2 mapping from previously measured T1 and B1 maps, and bSSFP images with at least two phase offsets and two flip angles (=4 datasets, 8 min scan). Magn Reson Med 76:1790–1804, 2016. © 2015 International Society for Magnetic Resonance in Medicine